Design and implementation of automatic number plate recognition on android platform - Mutholib, Abdul; Gunawan, Teddy Surya; Kartiwi, Mira (2012)
Android platform has gained popularity in recent years in terms of market share and number of available applications. Android operating system is built on a modified Linux kernel with built-in services such as email, web browser, and map applications. In this paper, automatic number plate recognition (ANPR) was designed and implemented on Android mobile phone platform. First, the graphical user interface (GUI) for capturing image using built-in camera was developed to acquire car plate number in Malaysia. Second, the preprocessing of raw image was done using contrast enhancement, filtering, and straightening. Next, an optical character recognition (OCR) using neural network was utilized to extract texts and numbers. The proposed ANPR algorithm was implemented and simulated using Android SDK on a computer. The preliminary results showed that our system is able to recognize most of the plate characters by almost 88%. Future research includes optimizing the system for mobile phone implementation with limited CPU and memory resources, and geo-tagging of the image using GPS coordinates and online database for various mobile applications.